2008
DOI: 10.1038/oby.2008.53
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Subsets of Hypothalamic Genes Are Modulated by Two Different Thermogenesis‐inducing Stimuli

Abstract: Obesity results from an imbalance between food intake and energy expenditure, two vital functions that are tightly controlled by specialized neurons of the hypothalamus. The complex mechanisms that integrate these two functions are only beginning to be deciphered. The objective of this study was to determine the effect of two thermogenesis-inducing conditions, i.e., ingestion of a high-fat (HF) diet and exposure to cold environment, on the expression of 1,176 genes in the hypothalamus of Wistar rats. Hypothala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
2
9
0
1
Order By: Relevance
“…In fact, a low-protein diet was reported to result in reduced activation of satiety centers, leading to increased food intake (Du et al 2000). In the offspring of dams submitted to a protein-restricted diet, during gestation and lactation, hyperphagia associated with an increased expression of NPY and AgRP in the hypothalamus was described (De Souza et al 2008;Orozco-Solis Fig. 3 Food intake profile and hypothalamic STAT3 activation in response to leptin in mice that underwent protein-restriction with or without HFD and Tau supplementation.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, a low-protein diet was reported to result in reduced activation of satiety centers, leading to increased food intake (Du et al 2000). In the offspring of dams submitted to a protein-restricted diet, during gestation and lactation, hyperphagia associated with an increased expression of NPY and AgRP in the hypothalamus was described (De Souza et al 2008;Orozco-Solis Fig. 3 Food intake profile and hypothalamic STAT3 activation in response to leptin in mice that underwent protein-restriction with or without HFD and Tau supplementation.…”
Section: Discussionmentioning
confidence: 97%
“…It is tempting to speculate that the interaction between ASP and MSG may converge at the level of the NMDA receptor for which glutamate and aspartate are both ligands; however the situation is likely to be far more intricate. Glutamate is the most abundant excitatory neurotransmitter and plays a pivotal role in the formation of synapses, integration of convergent signals, the establishment of N-methyl-D-aspartate (NMDA) receptor-dependent long term potentiation, and several critical autonomic functions including appetite regulation and thermogenesis [55]. However, elevated levels of glutamate have been shown to cause selective neuronal damage in the brains of infant mice, in particular the highly vascularized areas located outside the blood–brain barrier such as the median eminence and the hypothalamic arcuate nucleus [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, a number of cytokines were identified. Real-time PCR, ELISA and immunoblot demonstrated that expressions of tumor necrosis factor (TNF)-␣ , interleukin-1 ␤ and interleukin-6 were significantly increased in the hypothalamus of rats fed on a high-fat diet [16,22] .…”
Section: Diet-induced Expression Of Cytokines In the Hypothalamusmentioning
confidence: 99%
“…Interestingly, analyzing the genes modulated by functional clustering revealed that the majority of the genes undergoing differential expression belong to families of genes with immunological function [22] . Among these, a number of cytokines were identified.…”
Section: Diet-induced Expression Of Cytokines In the Hypothalamusmentioning
confidence: 99%
See 1 more Smart Citation